European Society of Cardiology Working Group on Adult Congenital Heart Disease and Study Group for Adult Congenital Heart Care in Central and South Eastern European Countries consensus paper: current status, provision gaps and investment required - Brida, Margarita; Šimkova, Iveta; Jovović, Ljiljana; Prokšelj, Katja; Antonová, Petra; Balint, Hajnalka Olga; Gumbiene, Lina; Lebid, Ihor H; Komar, Monika; Kratunkov, Pencho; Kovačević Preradović, Tamara; Ermel, Raili; et al. (European journal of heart failure, 2021)
AIMS: To examine the current status of care and needs of adult congenital heart disease (ACHD) services in the Central and South Eastern European (CESEE) region. METHODS AND RESULTS: We obtained data regarding the national ACHD status for 19 CESEE countries from their ACHD representative based on an extensive survey for 2017 and/or 2018. Thirteen countries reported at least one tertiary ACHD centre with a median year of centre establishment in 2007 (interquartile range 2002-2013). ACHD centres reported a median of 2114 patients under active follow-up with an annual cardiac catheter and surgical intervention volume of 49 and 40, respectively. The majority (90%) of catheter or surgical interventions were funded by government reimbursement schemes. However, all 19 countries had financial caps on a hospital level, leading to patient waiting lists and restrictions in the number of procedures that can be performed. The median number of ACHD specialists per country was 3. The majority of centres (75%) did not have ACHD specialist nurses. The six countries with no dedicated ACHD centres had lower Gross Domestic Product per capita compared to the remainder (P = 0.005). CONCLUSION: The majority of countries in CESEE now have established ACHD services with adequate infrastructure and a patient workload comparable to the rest of Europe, but important gaps still exist. ACHD care is challenged or compromised by limited financial resources, insufficient staffing levels, and reimbursement caps on essential procedures compared to Western Europe. Active advocacy and increased resources are required to address the inequalities of care across the continent.
Keywords: dospělí; Consensus; kardiologie; srdeční selhání; Adult; Evropa; konsensus; lidé; Humans; Heart Defects, Congenital; Cardiology; Heart Failure; vrozené srdeční vady; Europe